Vaccine-induced immune thrombotic thrombocytopenia: Updates in pathobiology and diagnosis - Jevtic, Stefan D.; Arnold, Donald M.; Modi, Dimpy; Ivetic, Nikola; Bissola, Anna-Lise; Nazy, Ishac (Frontiers in Cardiovascular Medicine, 2022)
Coronavirus disease 2019 (COVID-19) is a viral respiratory infection caused by the severe acute respiratory syndrome virus (SARS-CoV-2). Vaccines that protect against SARS-CoV-2 infection have been widely employed to reduce the incidence of symptomatic and severe disease. However, adenovirus-based SARS-CoV-2 vaccines can cause a rare, thrombotic disorder termed vaccine-induced thrombotic thrombocytopenia (VITT). VITT often develops in the first five to thirty days following vaccination and is characterized by thrombocytopenia and thrombosis in unusual locations (e.g. cerebral venous sinus thrombosis). The diagnosis is confirmed by testing for anti-PF4 antibodies, as these antibodies are capable of platelet activation without any cofactor. It can be clinically challenging to differentiate VITT from a similar disorder called heparin-induced thrombocytopenia (HIT), since heparin is commonly used in hospitalized patients. VITT and HIT have similar pathobiology and clinical manifestations but important differences in testing including the need for PF4-enhanced functional assays and the poor reliability of rapid immunoassays for the detection of anti-platelet factor 4 (PF4) antibodies. In this review we summarize the epidemiology of VITT; highlight similarities and differences between HIT and VITT; and provide an update on the clinical diagnosis of VITT.